1990
DOI: 10.1111/j.1540-8159.1990.tb02078.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Symptoms after Ventricular Pacing in Unexplained Syncope

Abstract: We report clinical and hemodynamic data in two cases of recurrent syncope. Both patients received permanent demand ventricular pacing (VVI) for unexplained syncope. Both patients experienced recurrent syncope after pacemaker implantation. They later underwent 60 degrees head-up tilt testing, initially noninvasively and then with hemodynamic profile. A vasovagal response to tilt occurred with bradycardia and was complicated by the onset of ventricular pacing and retrograde atrioventricular conduction (RAVC) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…[17][18][19] There is also evidence that neurally-mediated syncope is a much greater clinical problem than is generally recognised. 20 21 A recent major European study of dual chamber pacing in patients with ''tilt positive'' cardioinhibitory syncope demonstrated that this treatment approach offers long term protection from recurrent syncope, but patient selection for pacing therapy remains challenging as even in untreated patients the burden of recurrence is low.…”
Section: Pacing For Neurally-mediated Syncopementioning
confidence: 99%
“…[17][18][19] There is also evidence that neurally-mediated syncope is a much greater clinical problem than is generally recognised. 20 21 A recent major European study of dual chamber pacing in patients with ''tilt positive'' cardioinhibitory syncope demonstrated that this treatment approach offers long term protection from recurrent syncope, but patient selection for pacing therapy remains challenging as even in untreated patients the burden of recurrence is low.…”
Section: Pacing For Neurally-mediated Syncopementioning
confidence: 99%
“…VVI (ventricular demand-inhibited) pacing has been unsuccessful in preventing symptoms. The loss of atrioventricular (AV) synchrony actually potentiates the hypotension [2,3]. AAI (atrial demand-inhibited) pacing would not be adequate due to the possibility of AV block or asystole during a vasovagal episode.…”
Section: Vasovagal Syncopementioning
confidence: 99%
“…In susceptible patients, hyperactivated C receptors can produce, via the tractus nucleus solitarius, a sudden withdrawal of sympathetic tone with enhanced parasympathetic activity, resulting in severe peripheral vasodilation (hypotension) and bradycardia leading to syncope. [3][4][5][14][15][16][17][18][19][20]31,32 These factors usually function by increasing the catecholamine discharge 18 and further enhancing inotropism. 14 In fact, most patients show a marked increase in heart rate and a low frequency/high frequency ratio that reflects sympathetic activity in heart rate variability immediately before vasovagal syncope during HUT testing.…”
Section: Discussionmentioning
confidence: 99%